Modelling Fixed Income Securities and Interest Rate Options. - Rich, Don; Jarrow, Robert A. (Journal of Finance, 1996)
Modeling Fixed Income Securities and Interest Rate Options, Third Edition presents the basics of fixed-income securities in a way that, unlike competitive texts, requires a minimum of prerequisites. While other books focus heavily institutional details of the bond market, all of which could easily be learned on the job, the third edition of this classic textbook is more focused with presenting a coherent theoretical framework for understanding all basic models. The author’s unified approach—the Heath Jarrow Morton model—under which all other models are presented as special cases, enhances understanding of the material. The author’s pricing model is widely used in today’s securities industry. This new edition offers many updates to align with advances in the research and requires a minimum of prerequisites while presenting the basics of fixed-income securities. Highlights of the Third Edition Chapters 1-16 completely updated to align with advances in research Thoroughly eliminates out-of-date material while advancing the presentation Includes an ample amount of exercises and examples throughout the text which illustrate key concepts .